The (True) Legacy of Two Really Existing Economic Systems - Dan Ariely; Ximena Garcia-Rada; Lars Hornuf; Heather Mann (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
By running an experiment among Germans collecting their passports or ID cards in the citizen centers of Berlin, we find that individuals with an East German family background cheat significantly more on an abstract task than those with a West German family background. The longer individuals were exposed to socialism, the more likely they were to cheat on our task. While it was recently argued that markets decay morals (Falk and Szech, 2013), we provide evidence that other political and economic regimes such as socialism might have an even more detrimental effect on individuals' behavior.
urn:nbn:de:bvb:19-epub-20974-4
Keywords: C93; D63; P51; 330; Experimental economics; cheating; cross-culture study